Obscure gastrointestinal bleeding resulting from small bowel neoplasia; A case series. (2019) - Teh, Jia Wei; Fowler, Amy L.; Donlon, Noel E.; Khan, Waqar; Khan, Iqbal Z.; Waldron, Michael; Barry, Kevin
Highlights: Obscure GI bleeding can be a challenging diagnosis and is well acknowledged. Perseverance is required to achieve the correct diagnosis in obscured GI bleeding. Diagnostic overshadowing can halt investigations and delay diagnosis. Multidisciplinary team input is important in the diagnosis of obscured GI bleeding. Abstract: Introduction: Undiagnosed gastrointestinal bleeding may originate in the small bowel. This presents a diagnostic challenge despite the advancement in contemporary imaging. We report two cases which highlight the limitations of routine investigation for obscure gastrointestinal bleeding. Presentation of case: Patient A presented with a history of rectal bleeding, treated with interventional embolisation of caecal angiodysplasia. A diagnosis of neuroendocrine tumour (NET) was reached two years after presentation following intraoperative right hemicolectomy resection of a presumed recurrent angiodysplastic bleed. Patient B presented with recurrent melaena labelled as non-steroidal anti-inflammatory drug (NSAID) induced gastritis. After multiple endoscopic and radiological investigations, a 4.5 cm mass was visualised on imaging after three years, which was histologically proven as gastrointestinal stromal tumour (GIST) of the small bowel. Both patients experienced a delayed diagnosis despite multiple investigations and careful follow-up. Discussion: Our case series discusses the benefits and limitations of investigation for gastrointestinal bleeding and suggests a need for continued multidisciplinary input in situations where the patient presumed diagnosis remains in question. Conclusion: OGIB remains a diagnostic challenge and is attributable to small bowel pathology in 75% of cases. This suggests a need for continued investigation in situations where the patient presents multiple times despite adequate treatment for the presumed underlying condition.